Co-infection of Ticks: The Rule Rather Than the Exception - Moutailler, Sara; Valiente Moro, Claire; Vaumourin, Elise; Michelet, Lorraine; Tran, Florence Hélène; Devillers, Elodie; Cosson, Jean-François; Gasqui, Patrick; Van, Van Tran; Mavingui, Patrick; Vourc’h, Gwenaël; Vayssier-Taussat, Muriel (PLOS Neglected Tropical Diseases, 2016)
Author Summary Ticks transmit more pathogens than any other arthropod, and one single species can transmit a large variety of bacteria and parasites. Because co-infection might be much more common than previously thought, we evaluated the prevalence of 38 known or neglected tick-borne pathogens in Ixodes ricinus ticks. Our results demonstrated that co-infection occurred in almost half of the infected ticks, and that ticks could be infected with up to five pathogens. Moreover, as it is well established that symbionts can affect pathogen transmission in arthropods, we also evaluated the prevalence of four symbiont species and demonstrated that all ticks were infected by at least one microorganism. This work highlights the co-infection phenomenon in ticks, which may have important implications for human and animal health, emphasizing the need for new diagnostic tests better adapted to tick-borne diseases. Finally, the high co-occurrence of symbionts and pathogens in ticks, reveals the necessity to also account for these interactions in the development of new alternative strategies to control ticks and tick-borne disease.